PERLINDUNGAN KONSUMEN ATAS JUAL BELI RUMAH DI KOTA MAKASSAR - Ashar Sinilele (El-Iqthisadi, 2020)
AbstractThe legal relationship that arises in the sale and purchase utilization of houses between consumers and developers not only takes place due to an agreement (binding sale and purchase agreement), but also arises because of the provisions of the law (legal engagement relationship). The legal relationship takes place at each transaction process/stage, both the pre-transaction stage, the transaction stage and the post/transactional stage. The legal relationship takes place at every transaction process/stage, so that legal protection must also be obtained by each consumer in each transaction stage. Legal protection for consumer rights in the process of buying and selling stages and ownership of residential houses has been regulated and stated in various legal provisions and legislation consisting of the Civil Code, Law number 8 of 1999 concerning Consumer Protection, Law number 4 of 1992 concerning Housing and Settlements, and Law Number 18 of 1999 concerning Construction Services. To realize consumer protection is carried out as a joint effort based on the principle of benefits, the principle of justice, the principle of balance, the principle of security and the principle of legal certainty.Keywords: Consumer Protection, Legal Relationship, Sale and Purchase.AbstrakHubungan hukum yang timbul dalam jual beli dan pemanfaatan rumah  antara konsumen dan developer tidak hanya berlangsung karena adanya perjanjian (perjanjian pengikatan jual beli) semata, tetapi juga timbul karena ketentuan undang-undang (hubungan hukum perikatan). Hubungan hukum tersebut berlangsung pada setiap proses/tahapan transaksi, baik tahap pra transaksi, tahap transaksi maupun tahap purna/pascatransaksi. Hubungan hukum tersebut berlangsung pada setiap proses/tahapan transaksi, sehingga perlindungan hukum harus pula diperoleh setiap konsumen dalam setiap tahapan transaksi. Perlindungan hukum atas hak-hak konsumen dalam proses tahapan jual beli dan pemilikan rumah tinggal telah diatur dan tercantum dalam berbagai ketentuan hukum dan perundang-undangan yang terdiri dari Kitab Undang-Undang Hukum Perdata, Undang-Undang No. 8 Tahun 1999 tentang Perlindungan Konsumen, Undang-Undang No. 4 Tahun 1992 tentang Perumahan dan Permukiman,  dan Undang-Undang Nomor 18 Tahun 1999 tentang Jasa Konstruksi. Untuk mewujudkan perlindungan konsumen diselenggarakan sebagai usaha bersama berdasarkan asas manfaat, asas keadilan, asas keseimbangan, asas keamanan dan asas kepastian hukum.Kata Kunci : Hubungan Hukum, Jual Beli, Perlindungan Konsumen.